PENERAPAN MEDIA BONEKA TANGAN UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN di TK ST THOMAS II MEDAN - Mei Lyna Girsang; Robinson Hutagaol; Jheni Yusuf Saragih; Veronika Halawa; Devensif Buulolo; Dwinur (LPPI UMN AL WASHLIYAH, 2026)
Early childhood speech skills need to be stimulated through engaging and interactive learning. Hand puppets can be a fun learning alternative, encouraging children to become more confident in communicating and retelling experiences or stories they hear. This community service activity aims to improve the speech skills of children aged 5–6 years through the application of hand puppets and to enhance teachers' skills in utilizing innovative learning media. The activity was implemented through outreach, training, mentoring on the application of hand puppets, and evaluation with teachers at St. Thomas I Kindergarten, Medan, involving 20 children in Group B. The use of hand puppets made learning more interactive. Children became more active, confident, and able to express ideas and retell stories in simple language. Teachers were also able to implement the media in learning activities. The use of hand puppets provided positive benefits in improving the quality of language learning and the speech skills of children aged 5–6 years.